ADOPTING BLOCKCHAIN FOR THE FUTURE IN THE TRANSFORMATION OF ACCOUNTING IN THE MODERN ERA - Briliant, Elsa Aurora; Hartana, Salma Palupi (PT Naureen Digital Education, 2025)
This study aims to analyze and compare user perceptions of blockchain technology implementation using samples from two different research journals. The research sample consisted of 400 respondents, with each journal presenting 200 respondents from previous research on blockchain implementation in the accounting sector. The study used a quantitative method with descriptive statistical analysis techniques and mean difference tests to evaluate differences in perception and acceptance levels of blockchain technology from two different research journals. The results of the study indicate that perceptions of the use of blockchain technology in the accounting sector have been fairly evenly applied by accountants in companies in Indonesia. However, companies that adopt blockchain are more focused on companies in large cities. This study concludes that user perceptions of blockchain technology vary based on the adoption landscape of variations across companies in Indonesia and that further study is needed to understand other factors that influence the acceptance of this technology across industries